Emotional Stabilization: Its Effect on Stress Reduction in Social Workers in Handling Sexual Violence Cases - Shonhaji, Shonhaji; Setiawan, Nugroho Arief; Musthafa, Fikrhatul Fitriyah (ANFUSINA: Journal of Psychology, 2024)
A social worker who works to deal with social problems that occur in the community is required to always be ready when facing then conducting case reports and assistance to victims, including in cases of sexual violence. However, work stress is one of the causes of less than optimal services provided by social workers to victims of sexual violence. This study aims to reduce stress levels in social workers who handle sexual violence cases. This type of research uses experimental research with a one group with pretest-posttest design. This research was conducted in three District or City Social Services in Lampung. The sample in this study amounted to 60 social workers who were taken using random sampling technique. Data analysis in the study used t-test (independent sample test) statistical analysis of the gain score (the difference between pretest and posttest). With the results of the normality test of both pretest and posttest data with normal distribution, then a paired sample test was conducted. The obtained value of t = 4.337 with sig.0.001 means that there is a significant difference in the stress level of social workers before emotional stabilisation training and after training, with the average value of the stress level of social workers before training is 25.17 while after training the average value drops to 17.38. The results showed that the psychological training ‘Emotion Stabilisation’ was significantly influential in reducing the stress level of social workers who handle sexual violence cases. The results of this study have important implications in the development of social worker empowerment programmes, especially in areas that are at high risk of psychological stress. Emotion management-based training such as ‘Emotion Stabilisation’ can be used as a routine programme to improve the welfare of social workers, especially those who handle sexual violence cases. Keywords: Emotional stabilisation, Stress Level, Social Worker, Sexual Violence